93 CHIRAL SEPARATION OF THE INOTROPIC AND CHRONOTROPIC ACTIONS OF DIGOXIN IN A CANINE MODEL. (1st March 2007) - Spies, C.; Gupta, A.; Glock, D.; Spoon, J.; Williams, L.; Ranade, V.; Snell, J.; Molnar, J.; Somberg, J. C.
Abstract : The digoxin molecule is chiral, having asymmetries at the C3 + C17 carbon centers that give rise to stereoscopic isomers. The actions of digoxin chiral isolates on cardiac conduction and contractility have been shown to differ in the guinea pig. Additional supplies of the chiral isolates were obtained through HPLC employing a cyclobond chiral column, separating digoxin into two distinct chromatographic peaks, each with a different retention time. The optical rotation of the two isolates were +17 and +3, respectively, with the same mass/change ratio (m/z) of 780, identical to racemate digoxin. The effects of the isolates were determined in 15 catheterized dogs anesthetized with isoflurane. The effects of the two chiral isolates were contrasted to digoxin for changes in HR, PR, and AH intervals, as well as left and right ventricular dp/dt. Digoxin and the isolates were infused at 1.5 μg/kg/min. Digoxin racemate caused a 15% slowing in HR at 45 minutes, a 15% increase in PR interval at 60 minutes, and a 20% increase in AH interval at 75 minutes. Dp/dtr was increased by 20% at 15 minutes and 50% at 60 minutes, whereas dp/dtL by 20% at 15 minutes and 50% at 105 minutes. Chiral isolate 1 failed to decrease HR or increase PR or AH intervals by 15%. Dp/dtr was increased by 50% at 15 minutes and dp/dtL by 20% at 15 minutes and 50% at 30 minutes. Isolate 2 slowed HR by 15% at 15 minutes and PR by 15% at 30 minutes, and AH decreased by 20% at 15 minutes, whereas dp/dtr was increased by 20% at 45 minutes and dp/dtL by 20% at 75 minutes; a 50% augmentation was not obtained. The contractility/conduction index (dose to 20% increase in dp/dt ÷ dose to 20% increase in AH interval) was 0.2 digoxin, < 0.125 chiral 1 and 3 for chiral 2. There is a marked difference between isolates 1 and 2 in AV conduction and contractile augmentation ( p < .001). Digoxin can be chirally separated, with one isolate causing progressive AV conduction delay and the other isolate predominantly causing contractile augmentation.